Therapeutic Lumbar Punctures in HIV-associated Cryptococcal Meningitis: should opening pressure direct management? - Kagimu, Enock; Engen, Nicole; Ssebambulidde, Kenneth; Kasibante, John; Kiiza, Tadeo K; Mpoza, Edward; L., Lillian Tugume; Nuwagira, Edwin; Nsangi, Laura; Meya, David B.; Rhein, Joshua; Abassi, Mahsa; et al. (In Open Forum Infectious Diseases., 2022)
Increased intracranial pressure (ICP) frequently complicates cryptococcal meningitis. Therapeutic lumbar punctures (LPs) have acute survival benefits in the first week, and we sought to understand the longer-term survival impact of therapeutic LPs. We prospectively enrolled HIV-seropositive adults with cryptococcal meningitis from 2013 to 2017 in Uganda. CSF opening pressure was measured at diagnosis. Therapeutic LPs were scheduled on days 3, 7, 10, 14, and performed additionally as clinically indicated. We assessed the association between clinical characteristics, CSF parameters, and 14- and 30-day mortality by baseline ICP. We also assessed 30-day mortality by number of follow-up therapeutic LPs performed within 7 days.
Keywords: Baseline Opening Pressure; Mortality; Therapeutic Lumbar Puncture